2020
DOI: 10.1038/s41398-020-00890-7
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin increases heart-rate variability in men at clinical high risk for psychosis: a proof-of-concept study

Abstract: Autonomic nervous system (ANS) dysfunction (i.e., increased sympathetic and/or decreased parasympathetic activity) has been proposed to contribute to psychosis vulnerability. Yet, we still lack directed therapeutic strategies that improve ANS regulation in psychosis or at-risk states. The oxytocin system constitutes a potential therapeutic target, given its role in ANS regulation. However, whether intranasal oxytocin ameliorates autonomic regulation during emerging psychosis is currently unknown. We pooled tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 108 publications
3
23
0
Order By: Relevance
“…Interestingly, the demonstrated OT-related changes in cross-frequency dynamics were shown to be paralleled by changes in ANS function, indicating a significant increase in high-frequency HRVan established marker of parasympathetic nervous system (PNS) 'rest-and-digest' autonomic function -as well as a decrease in low-frequency HRV -influenced by a mix of vagal, sympathetic nervous system (SNS) activity, and baroreflex mechanisms (Shaffer et al, 2014). These observations are in line with four prior studies, showing an increase in resting-state high-frequency HRV after a singledose of OT (Jain et al, 2017;Kemp et al, 2012;Martins et al, 2020;Norman et al, 2011). One study with chronic back pain patients showed no effect of OT on rest HRV, but here, small decreases in both high-and low-frequency HRV were noted during a mental arithmetic task, suggesting that OT differentially impacted HRV depending on whether the task context entailed a resting state or a state of (mild) cognitive stress (Tracy et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the demonstrated OT-related changes in cross-frequency dynamics were shown to be paralleled by changes in ANS function, indicating a significant increase in high-frequency HRVan established marker of parasympathetic nervous system (PNS) 'rest-and-digest' autonomic function -as well as a decrease in low-frequency HRV -influenced by a mix of vagal, sympathetic nervous system (SNS) activity, and baroreflex mechanisms (Shaffer et al, 2014). These observations are in line with four prior studies, showing an increase in resting-state high-frequency HRV after a singledose of OT (Jain et al, 2017;Kemp et al, 2012;Martins et al, 2020;Norman et al, 2011). One study with chronic back pain patients showed no effect of OT on rest HRV, but here, small decreases in both high-and low-frequency HRV were noted during a mental arithmetic task, suggesting that OT differentially impacted HRV depending on whether the task context entailed a resting state or a state of (mild) cognitive stress (Tracy et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This notion is important, considering that context and state-dependent changes are highlighted as important factors for inducing variations in OT's neuromodulatory effects (e.g. differential effects on rest (Jain et al, 2017;Kemp et al, 2012;Martins et al, 2020;Norman et al, 2011) versus task-related HRV (Tracy et al, 2018)). In this view, it has been suggested that OT may primarily promote the restoration of autonomic balance (enhanced PNS drive) in the relative absence of acute stressors, but that opposite effects may be induced in task contexts that induce (mild) states of acute stress, in which case a facilitation of SNS-driven arousal and attentional salience may be evident (Carter, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, intranasal oxytocin increased HF-HRV in CHR-P only. These findings support the need for further research to investigate the therapeutic potential of intranasal oxytocin ( Martins et al, 2020 ). Hippocampal dysfunction (HD) was investigated as a crucial factor for psychosis onset.…”
Section: Clinical Studies Of Treating Psychotic Disorder Using Intran...supporting
confidence: 67%
“…In women at the third trimester of pregnancy and during low-risk labor, application of OT increases vagally mediated activity ( Reyes-Lagos et al, 2015 ). IAO increases high frequency HRV (an index of cardio-parasympathetic activity) in men at clinical high risk for psychosis ( Martins et al, 2020 ) and with 38 men either receiving 24 IU OT intranasally or a placebo spray. While accomplishing an emotion classification task, electrodermal responses are measured as an index of sympathetic activity.…”
Section: Regulation Of Sensorimotor Activitymentioning
confidence: 99%